Sekolah Etnis Tionghoa Di Jakarta Pada Masa Pemerintahan Presiden Soeharto (1966-1998) - Dwi Sudibyo; Sumaryoto Sumaryoto; Sumaryati Sumaryati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
The purpose of the study was to find out the social, economic and educational conditions of the Chinese community in the early days of President Soeharto's administration; to find out the policies of President Soeharto's administration towards the Chinese ethnic group in Jakarta in the field of education; to find out the development of Chinese ethnic schools in Jakarta during the late days of President Soeharto's administration in Jakarta; Based on the results of the study: 1) That after the 1950s, the government of the Republic of Indonesia tried to build Indonesia's economic life. One way is to develop indigenous entrepreneurs; 2) That Chinese politics during the New Order era was a